Determining the opacity of urinary stone using only the Computed Tomography imaging, Is KUB still needed? - Masoumi, Navid; Faghihi Langroudi, Taraneh; Bagheri, Fahimeh; Alirezaei, Amirhesam; Ali Asgari, Majid; Dehghani, Mehdi (Archives of Men's Health, 2021)
Introduction: Defining the opacity of urinary stones by Kidney -Ureter-Bladder (KUB) imaging in the selection of treatment modality is considered necessary by many urologists. This imposes more radiation to patients and additional health costs. The objective of this study is evaluation of the capability of Computed Tomography (CT) imaging in predicting the opacity of urinary calculi. Methods: In this prospective study, the appearance of stones and the body characteristics of all our patients were recorded and analyzed. The setup for reviewing the imaging was as follows: first: CT-scout, then KUB and finally CT scan. The sensitivity and specificity of the CT-scout and Hounsfield unit in detecting stone opacity was calculated. The effect of stone size and body parameters in CT on predicting non-opaque stones were then analyzed. CT scout-negative KUB-positive urolithiasis were analyzed separately. Results: Among 197 participants, all opaque calculi in CT scout were also visible on KUB. Among scout-negative urinary stones, twenty-eight (14.21%) were KUB opaque. For predicting the opacity by CT scan parameters, the most desirable HU cut-off was 504 HU and 510 HU in KUB and CT scout, with 80.8% and 86.5% sensitivity, respectively. The overall sensitivity of CT-scout was 86.27% and specificity was 64.29%. Stone diameter ≥5mm and subcutaneous fat width of ≤25.40 mm augmented the sensitivity in our study groups. Conclusion: All opaque calculi on scout imaging are also opaque on KUB and this could obviate the necessity of KUB imaging in this group of patients. HU above 504 in scout-negative stones has the best sensitivity and specificity in foretelling the opacity of stones and size ≥5mm and subcutaneous fat width of ≤25.40 mm augment their predictability potential.